Jesus as Goat of the Day of Atonement in Recent Synoptic Gospels Research - Moscicke, Hans (Currents in biblical research, 2018)
Do the Synoptic passion narratives portray Jesus (and Barabbas) as one (or both) of the goats of the Day of Atonement? This question currently has no consensus in biblical scholarship but four contrasting positions: The evangelists portray (1) Jesus as the abused scapegoat in his maltreatment by the Roman soldiers (Mk 15.16-20 parr.); (2) Jesus as a pharmakos-like scapegoat patterned after Hellenistic motifs of redemptive suffering; (3) Barabbas as the scapegoat and Jesus as the immolated goat (Mt. 27.15-26 parr.); and (4) Jesus as neither goat, but the typological fulfillment of alternative (suffering) figures: Isaiah's Servant, the Psalms' Righteous Sufferer, the Son of Man, and the divine warrior. This article reviews and evaluates these four positions, suggesting avenues for future research.